The Juridical Perspective of Islamic Law on Football Player Transfer Transactions: The Case of Persid Jember FC - Achmad Muthiurrohman; Moh. Bahrul Ulum; Y. A Triana Ohowaitun; Dominikus Rato (Rechtenstudent, 2026)
This research explores the legal aspects of football player transfer transactions in Indonesia, with a focus on Persid Jember. In practice, many transactions involving professional and semi-professional players lack clear contractual agreements, raising concerns about legal certainty. The study formulates two research questions: (1) How is the mechanism of player transfer conducted in Persid Jember? (2) How does Islamic law view the practice of player transfer at Persid Jember? The purposes of this study are to identify whether the mechanism of player transfers in Persid Jember aligns with valid contractual principles and to analyze the practice from the perspective of Islamic law. Using an empirical legal research method, data were collected through interviews, observations, and documentation. The findings show that Persid Jember recruits players through open selection and by signing players from other clubs whose contracts have expired. From the perspective of Islamic law, this practice is permissible because it follows the principles of ijarah (leasing contract), in which one party acts as the lessor (mu’ājir) and the other as the lessee (musta’jir). The validity of the transaction is reinforced by mutual consent and cooperation, fulfilling the essential elements of ijarah.